The Social Construction of Athlete Leadership: An Exploratory Case Study of the University of Southern California Women's Soccer Team - Ulrich, Cassandra (2018)
Studies of sport leadership have primarily focused on sport management and leadership at the administrative and coach level and have predominantly applied existing frameworks. The perspectives of the athletes and their understandings of leadership have been mostly unexamined. This study examines how leadership is socially constructed in high-performance collegiate sports teams by focusing on the student-athletes’ understandings of leadership and how their understandings were developed. Within a social constructionist theoretical framework, this dissertation provides a critical analysis of student-athletes’ understandings of leadership as members of one high-performance collegiate sports team. The study utilised a qualitative semistructured interview approach for data collection. The data sample consisted of 5 female players from the 2016 NCAA women’s soccer national championship team, the University of Southern California. The interviews were thematically analysed manually and guided by grounded theory. The analysis showed three key themes including the relationship between the on-field and off-field context and leadership, the current understanding of athlete leadership as purpose and role driven, and finally, how leadership is actively ‘done’ through leadership designations, education and status. Ultimately, this research has shown status as central to the construction of leadership as a negotiated, collective and relational process; the assumptions attached the status reflect assumptions about the nature of leadership. This dissertation argues that in order to understand and develop leadership within a high-performance collegiate sports team, then the barriers of status must be known.